Dystrophic Muscle in Mice Chimeric for Expression of α5 Integrin - Taverna, Daniela (The Rockefeller University Press, 1998)
α5-deficient mice die early in embryogenesis (Yang et al., 1993). To study the functions of α5 integrin later in mouse embryogenesis and during adult life we generated α5 −/−;+/+ chimeric mice. These animals contain α5-negative and positive cells randomly distributed. Analysis of the chimerism by glucose- 6-phosphate isomerase (GPI) assay revealed that α5 −/− cells contributed to all the tissues analyzed. High contributions were observed in the skeletal muscle. The perinatal survival of the mutant chimeras was lower than for the controls, however the subsequent life span of the survivors was only slightly reduced compared with controls (Taverna et al., 1998). Histological analysis of α5 −/−;+/+ mice from late embryogenesis to adult life revealed an alteration in the skeletal muscle structure resembling a typical muscle dystrophy. Giant fibers, increased numbers of nuclei per fiber with altered position and size, vacuoli and signs of muscle degeneration–regeneration were observed in head, thorax and limb muscles. Electron microscopy showed an increase in the number of mitochondria in some muscle fibers of the mutant mice. Increased apoptosis and immunoreactivity for tenascin-C were observed in mutant muscle fibers. All the alterations were already visible at late stages of embryogenesis. The number of altered muscle fibers varied in different animals and muscles and was often increased in high percentage chimeric animals. Differentiation of α5 −/− ES cells or myoblasts showed that in vitro differentiation into myotubes was achieved normally. However proper adhesion and survival of myoblasts on fibronectin was impaired. Our data suggest that a novel form of muscle dystrophy in mice is α5-integrin-dependent.